استخلاص (سائل – سائل) لعنصري الكوبالت والنيكل بواسطة: حمض الفوسفوريك، حمض الفوسفونيك وحمض الفوسفنيك (Latakia University Journal -Basic Sciences Series, 2018)
تمت دراسة استخلاص عنصري الكوبالت (II) والنيكل (II) بواسطة الأحماض العضوية الالكليلية: حمض الفوسفور ثنائي الالكليلD2EHPA ، حمض الفوسفونيك (RD577) وحمض الفوسفنيك (CNX) في وسط من الكسيلين. بيّنت النتائج أن استخلاص عنصر الكوبالت في الأحماض العضوية الثلاث قد تم عند قيم pH أكثر انخفاضاً مقارنة باستخلاص عنصر النيكل، كما أن عامل الفصل  تزايد حسب الترتيب: حمض الفوسفنيك > حمض الفوسفونيك > حمض الفوسفوريك أعطت طرائق تحليل ميل المنحنيات لعامل التوزيع (D) صيغاً لمعقدات الكوبالت والنيكل المستخلصة في الوسط العضوي تمثلت بـ  Co(HA2)2 وNi(HA2) (H2A2)x (H2O)2-x على التسلسل، حيث H2A2 تمثل جزيئات الحمض العضوي المستخلص بشكله الديمري و. The Solvent Extraction of Cobalt (II) and Nickel (II) by Xylene Solvations of Organic-Alkylphosphorus Acids: Dialkyl-Phosporic (D2EHPA), Phosphonic (RD577) and Phosphinic Acids (CNX) have been investigated. The Results Showed that cobalt is extracted in each organic acid, at lower pH Values have been investigated, compared to extraction of nickel, the cobalt-nickel separation increases in the order: Phosporoic < Phosphonic < Phospinic acids Application of the slope analysis technique indicates Stoichiometries of Co(HA2)2 and Ni(HA2)2(H2A2)x(H2O)2-x for the cobalt and nickel complexes, respectively, where H2A2 represents the dimerized extractant molecule and x = 0, 1 or 2.